DFIG-based offshore wind power plant connected to a single VSC-HVDC operated at variable frequency: Energy yield assessment. (15th June 2015) - De-Prada-Gil, Mikel; Díaz-González, Francisco; Gomis-Bellmunt, Oriol; Sumper, Andreas
Abstract: The existence of HVDC (High Voltage Direct Current) transmission systems for remote offshore wind power plants allows devising novel wind plant concepts, which do not need to be synchronized with the main AC grid. This paper proposes an OWPP (offshore wind power plant) design based on variable speed wind turbines driven by DFIGs (doubly fed induction generators) with reduced power electronic converters connected to a single VSC-HVDC converter which operates at variable frequency and voltage within the collection grid. It is aimed to evaluate the influence of the power converter size and wind speed variability within the WPP on energy yield efficiency, as well as to develop a coordinated control between the VSC-HVDC converter and the individual back-to-back reduced power converters of each DFIG-based wind turbine in order to provide control capability for the wind power plant at a reduced cost. To maximise wind power generation by the OWPP, an optimum electrical frequency search algorithm for the VSC-HVDC converter is proposed. Both central wind power plant control level and local wind turbine control level are presented and the performance of the system is validated by means of simulations using MATLAB/Simulink ® . Highlights: Influence of converter size and wind speed variability on energy capture efficiency. Coordinated control between a VSC-HVDC and DFIG WTs with reduced power converters. Static and dynamic analysis of the performance of the implemented control scheme. Optimal variable frequency operation to maximize WPP generation at a reduced cost.